Efektivitas Pelaksanaan Bimbingan Pemustaka pada Mahasiswa Institut Agama Islam Negeri (IAIN) Bengkulu - Sutriono, Sutriono (TIK ILMEU : Jurnal Ilmu Perpustakaan dan Informasi, 2017)
IAIN Bengkulu Library Center as a supporting partner of Tri Dharma Perguruan Tinggi every year has a work program or activity either directly or indirectly in providing guidance to the scalper pemustaka especially new students to introduce and direct the pemustaka to be able to recognize and use the facilities and information that has been provided in IAIN Bengkulu Library Center well, effectively, efficiently, orderly and independently. The effectiveness of librarian guidance done by librarian of IAIN Bengkulu Library Center from some description of the answer from informant IAIN Bengkulu informant and direct observation writer that guidance pemustaka contribute effectively to provide understanding and direction about utilization of library resources and able to minimize violations such as destruct the composition of book On the shelves, late return of books and create an orderly library, discipline in accessing information in the library